PENGARUH INFLASI TERHADAP PERTUMBUHAN EKONOMI PROVINSI ACEH PERIODE 2015- 2018 DALAM PRESPEKTIF EKONOMI ISLAM - Rahma Yulianti; Khairuna Khairuna (University Muhammadiyah Aceh, 2019)
The purpose of this study was to study the effect of inflation on the economic growth of Aceh Province in the 2015-2018 fiscal year. Inflation is measured by CPI (Consumer Price Index), economic growth is measured by GDP. The population in this study is on data and information regarding CPI allocation, and GDP in the economic sector. This study uses the Konumen Price Index data, and economic growth data seen from the survey conducted by BPS in the 2015-2018 fiscal year, and uses the census method. For hypothesis testing, this study uses simple linear regression analysis. The test results show that, inflation affects economic growth. The coefficient of determination is 29.4. The coefficient of determination that has been calculated is 29.4% included in the criteria of the role that is quite high, in accordance with the Guidelines for Providing Interpretation of the Coefficient of Determination. So that it can be concluded that inflation affects the economic growth of Aceh Province is high.